Learning to Extract Cross-Session Search Tasks - Song, Yang; Chang, Ming-Wei; He, Xiaodong; White, Ryen W.; Chu, Wei; Wang, Hongning (International World Wide Web Conference (WWW), 2013)
Search tasks comprising a series of search queries serving the same information need, have recently been recognized as an accurate atomic unit for modeling user search intent. Most prior research in this area has focused on short-term search tasks within a single search session, and heavily depend on human annotations for supervised classification model learning. In this work, we target the identification of long-term, or cross-session, search tasks (transcending session boundaries) by investigating inter-query dependencies learned from users' searching behavior. A semi-supervised clustering model is proposed based on the latent structural SVM framework, and a set of effective automatic annotation rules are proposed as weak supervision to release the burden of manual annotation. Experimental results using a large-scale search log of real user behavior collected from Bing.com confirms the effectiveness of the proposed model in identifying cross-session search tasks and the utility of the introduced weak supervision signals. Our learned model enables a more comprehensive understanding of search behavior via search logs and facilitates the development of dedicated search-engine support for long-term tasks.